Determinants of Post-Training Performance at PT Sinergi Unggul Berdikari: The Impact of Competence, Motivation, and Work Discipline - Sigit Perdana Kusuma; Yuni Pratikno; Kemal Taufik; Iwan Kurniawan (Indonesian Journal Economic Review (IJER), 2026)
This study aims to analyze the effects of competence, motivation, and work discipline on the performance of post-training participants at PT Sinergi Unggul Berdikari (Inera Learning Center). A quantitative associative approach was employed using a survey method. The sampling technique applied was saturated sampling, which included 60 alumni respondents from the technical guidance program conducted between July and December 2025. Primary data were collected through questionnaires and analyzed using Multiple Linear Regression techniques with statistical software. The statistical results indicate that, individually, motivation has a positive and significant impact on performance, with a t-count exceeding the t-table value (2.256 > 2.003). Work discipline also demonstrates a significant effect, emerging as the most dominant variable, with a t-count greater than the t-table value (3.549 > 2.003). Conversely, competence does not show a significant individual effect on performance (t-count -0.139 < t-table 2.003), which can be attributed to structural barriers stemming from bureaucratic inertia within the respondents' home institutions. Collectively, competence, motivation, and work discipline significantly influence performance, contributing 32.5% to the variance. This underscores the necessity for institutions to design training programs that enhance intrinsic motivation and to foster an innovative environment supported by institutional leaders, enabling alumni to optimally apply their technical competencies for superior performance.